(3GdMX GdChaQ aj GdML GdCcHQs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdcHjQ GdCcHQGdPi CfYe Ydi YHGOg CeG HYO ajbhd bO SCdfi HYV HjGf eG ETJgQ Ydi CdSfg fhY GdEfSGf ef EWdGb GdML GdCcHQ Ydi NUhU GdML GdebjO s
(3BNQgG (B:s
(3ceG jOd Ydjg eG ai UMjM eSde Yfg Cfg QCi ehSi hjhfS YdjgeG GdSdGe ajeG Hjf GdMQejf GdTQjajf eMQejf edHjf eJVQYjf adG QjH Gfg HgPG GdefUH ai ReGf hdGjJg Chdi Gddge Udi Ydi SjOfG eMeO UdGI Jchf dc QVGA hdMbg COGA hGLRGg YfG HHQcJg CaVd eG LRjJ fHs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B25s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs